2019
DOI: 10.1002/alr.22482
|View full text |Cite
|
Sign up to set email alerts
|

Rate of rhinosinusitis and sinus surgery following a minimally destructive approach to endoscopic transsphenoidal hypophysectomy

Abstract: Background There remains considerable variation in the extent of sinonasal preservation during the approach for endoscopic transsphenoidal hypophysectomy (TSH). We advocate for a minimally destructive approach utilizing turbinate lateralization, small posterior septectomy, no ethmoidectomy, and preservation of nasoseptal flap (NSF) pedicles bilaterally. Due to these factors, this approach may affect the rates of postoperative rhinosinusitis. The objective of this study is to define the rates of postoperative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Multiple studies have demonstrated initial increases in SNOT-22 at the first postoperative visit after endoscopic skull base surgery, followed by gradual improvements over time. [43][44][45] Of these studies, two utilized some form of nasal packing consistently, whereas one systematic review did not report frequency of nasal packing utilized. Taken with the findings from Little et al, which revealed decreased quality of life in the immediate postoperative period in association with nasal splints and packing.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated initial increases in SNOT-22 at the first postoperative visit after endoscopic skull base surgery, followed by gradual improvements over time. [43][44][45] Of these studies, two utilized some form of nasal packing consistently, whereas one systematic review did not report frequency of nasal packing utilized. Taken with the findings from Little et al, which revealed decreased quality of life in the immediate postoperative period in association with nasal splints and packing.…”
Section: Discussionmentioning
confidence: 99%
“…nasal mucosa with resultant crusting, nasal block, sinusitis and epistaxis occur. 14,[17][18][19][20] The two major endoscopic techniques in current practice are the uni-nostril and bi-nostril approaches, 3,6,10,21 both being safe and effective in pituitary surgery, although the bi-nostril approach may be preferred when an extended approach is required. 3,6,21 While the deterioration in QoL is probably transient, there are no prospective studies comparing the nasal outcomes between the two approaches.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Instruments that have been utilized for assessment of QoL following endoscopic pituitary surgery include Anterior Skull Base Nasal Inventory-12 (ASK Nasal-12), 22,41 SNOT 22, 14,[18][19][20]41 SNOT 20, 13 VAS, 13 SF-36, 42 and WHO-QoL BREF. 43 The ASK-12 is a site specific 12 question inventory which focuses on sinonasal morbidity and evaluates all likely This article is protected by copyright.…”
Section: Assessing Sinonasal Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggest further in vivo studies to assess the impact of ROC on the full process of wound healing because the length of exposure was limited. Rimmer et al 9 . report a retrospective review of 415 patients who underwent endoscopic transsphenoidal hypophysectomy (TSH) via a “minimally destructive approach” (utilizing middle turbinate lateralization, small posterior septectomy without ethmoidectomy, and preservation of the nasoseptal flap) to determine the rate of postoperative rhinosinusitis.…”
mentioning
confidence: 99%